110k views
2 votes
I need help on this I am just going to use the picture

I need help on this I am just going to use the picture-example-1

2 Answers

4 votes

D is the correct answer

User Santana
by
4.5k points
3 votes

Answer:

D

Explanation:

let y = f(x), that is

y =
(2x-3)/(5)

Rearrange making x the subject

Multiply both sides by 5

5y = 2x - 3 ( add 3 to both sides )

5y + 3 = 2x (divide both sides by 2 ) , then

x =
(5y+3)/(2)

Change y back into term of x, hence


f^(-1)(x) =
(5x+3)/(2) → D

User Car
by
4.6k points